Note on the Stability of a Slowly Rotating Timoshenko Beam with Damping (Advances in Applied Mathematics and Mechanics, 2021)
This paper continues the senior author's previous investigation of the slowlyrotating Timoshenko beam in a horizontal plane whose movement is controlled bythe angular acceleration of the disk of the driving motor into which the beam is rigidlyclamped. It was shown before that this system preserves the total energy. We considerthe problem of stability of the system after introducing a particular type of damping.We show that the energy of only part of the system vanishes. We illustrate obtainedsolution with the critical case of the infinite value of the damping coefficient.